Wahrheit, Freiheit, Demokratie – Zum Umgang mit Hochwertausdrücken in rechtspopulistischen bzw. neurechten Argumentationen anhand des Blogs „Politically Incorrect“ - Markewitz, Friedrich (Türkisch-Deutsche Studien Jahrbuch 2019:Migration movements and right-wing populism after 2015)

Generalized transitivity: A systematic comparison of concepts with an application to preferences in the Babington Smith model - Haddenhorst, Björn; Hüllermeier, Eyke; Kolb, Martin (International Journal of Approximate Reasoning)
Reciprocal relations are binary relations Q with entries Q(i,j)∈[0,1], and such that Q(i,j)+Q(j,i)=1. Relations of this kind occur quite naturally in various domains, such as preference modeling and preference learning. For example, Q(i,j) could be the fraction of voters in a population who prefer candidate i to candidate j. In the literature, various attempts have been made at generalizing the notion of transitivity to reciprocal relations. In this paper, we compare three important frameworks of generalized transitivity: g-stochastic transitivity, T-transitivity, and cycle-transitivity. To this end, we introduce E-transitivity as an even more general notion. We also use this framework to extend an existing hierarchy of different types of transitivity. As an illustration, we study transitivity properties of probabilities of pairwise preferences, which are induced as marginals of an underlying probability distribution on rankings (strict total orders) of a set of alternatives. In particular, we analyze the interesting case of the so-called Babington Smith model, a parametric family of distributions of that kind.

Auswirkungen der Digitalisierung industrieller Arbeit auf die allgemeine und berufliche Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung und Berufsbildung 4.0 am Übergang Schule - Beruf)

Das Öffnen und Teilen von Daten qualitativer Forschung: eine Handreichung - Steinhardt, Isabel; Fischer, Caroline; Heimstädt, Maximilian; Hirsbrunner, Simon David; Ikiz-Akinci, Dilek; Kressin, Lisa; Kretzer, Susanne; Möllenkamp, Andreas; Portzelt, Maike; Rahal, Rima-Maria; Schimmler, Sonja; Wilke, René; et al.

Learning Open Science by doing Open Science. A reflection of a qualitative research project-based seminar - Steinhardt, Isabel (Education for Information)
Openness in science and education is increasing in importance within the digital knowledge society. So far, less attention has been paid to teaching Open Science in bachelor’s degrees or in qualitative methods. Therefore, the aim of this article is to use a seminar example to explore what Open Science practices can be taught in qualitative research and how digital tools can be involved. The seminar focused on the following practices: Open data practices, the practice of using the free and open source tool “Collaborative online Interpretation, the practice of participating, cooperating, collaborating and contributing through participatory technologies and in social (based) networks. To learn Open Science practices, the students were involved in a qualitative research project about “Use of digital technologies for the study and habitus of students”. The study shows the practices of Open Data are easy to teach, whereas the use of free and open source tools and participatory technologies for collaboration, participation, cooperation and contribution is more difficult. In addition, a cultural shift would have to take place within German universities to promote Open Science practices in general.
Keywords: Open Science; Open Education Practices; Library and Information Sciences; Education; Information Systems

Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Effects of 21 days of bed rest and whey protein supplementation on plantar flexor muscle fatigue resistance during repeated shortening contractions - Bosutti, Alessandra; Mulder, Edwin; Zange, Jochen; Bühlmeier, Judith; Ganse, Bergita; Degens, Hans (European Journal of Applied Physiology)
Abstract Purpose Space flight and bed rest (BR) lead to a rapid decline in exercise capacity. Whey protein plus potassium bicarbonate diet-supplementation (NUTR) could attenuate this effect by improving oxidative metabolism. We evaluated the impact of 21-day BR and NUTR on fatigue resistance of plantar flexor muscles (PF) during repeated shortening contractions, and whether any change was related to altered energy metabolism and muscle oxygenation. Methods Ten healthy men received a standardized isocaloric diet with ( n = 5) or without ( n = 5) NUTR. Eight bouts of 24 concentric plantar flexions (30 s each bout) with 20 s rest between bouts were employed. PF muscle size was assessed by means of peripheral quantitative computed tomography. PF muscle volume was assessed with magnetic resonance imaging. PF muscle force, contraction velocity, power and surface electromyogram signals were recorded during each contraction, as well as energy metabolism ( 31 P nuclear magnetic resonance spectroscopy) and oxygenation (near-infrared spectroscopy). Cardiopulmonary parameters were measured during an incremental cycle exercise test. Results BR caused 10–15% loss of PF volume that was partly recovered 3 days after re-ambulation, as a consequence of fluid redistribution. Unexpectedly, PF fatigue resistance was not affected by BR or NUTR. BR induced a shift in muscle metabolism toward glycolysis and some signs of impaired muscle oxygen extraction. NUTR did not attenuate the BR-induced-shift in energy metabolism. Conclusions Twenty-one days’ BR did not impair PF fatigue resistance, but the shift to glycolytic metabolism and indications of impaired oxygen extraction may be early signs of developing reduced muscle fatigue resistance.
Keywords: Physiology (medical); Public Health; Environmental and Occupational Health; Orthopedics and Sports Medicine; General Medicine; Public Health; Environmental and Occupational Health; Physiology

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Weiße Normalität. Perspektiven einer postkolonialen Literaturdidaktik - Kißling, Magdalena

Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters - Steigerwald, Jörn (Das Theater der Zärtlichkeit)

Von der heroischen Tragödie zum (bürgerlichen) Trauerspiel. Gattungspoetische Selbstreflexion in Lessings "Miss Sara Sampson“ - Süwolto, Leonie (Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters (1630-1760))

Von Arsene zu Emilia - Transformationen des zivilen Klassizismus oder Gattung und Geschlecht bei Deschamps, Gottsched und Lessing - Süwolto, Leonie (Komparatistik heute. Aktuelle Positionen der Komparatistik)

Aktuelle Positionen der Komparatistik

Molières Begründung der grande comédie als comédie tendre: Die zärtliche Liebesbeziehung in der École des femmes - Debisow, Adelina (Das Theater der Zärtlichkeit : Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters (1630-1760))

Tragische tendresse: Racines Andromaque - Schlieper, Hendrik (Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters (1630-1760). (culturae, 18))

Peers als Quelle aktueller Motivation? - Knickenberg, Margarita; Zurbriggen, Carmen; Schmidt, Philipp (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung. Die Relevanz von Peers für die Entwicklung von Jugendlichen konnte in verschiedenen Studien bereits bestätigt werden. Im Unterricht zeigt sich dies u.a. durch höhere situative Motivation und Freude sowie geringerem Stressempfinden während sozialer Interaktionen mit Mitschülerinnen und -schülern verglichen mit Einzelarbeitssituationen. Allerdings stellte sich auch heraus, dass Jugendliche mit Verhaltensauffälligkeiten Schwierigkeiten im Knüpfen und Aufrechterhalten von sozialen Kontakten und Freundschaften haben. Während in bisherigen Studien Verhalten als dichotome Variable untersucht wurde, wird hier ein dimensionaler, personzentrierter Ansatz zur Identifizierung von Gruppen mit heterogenen Verhaltensweisen verfolgt. Ziel dieses Beitrags ist daher die Untersuchung von Effekten sozialer Interaktionen im Unterricht auf das emotionale Erleben von Jugendlichen mit heterogenen Verhaltensweisen. Zudem wird ein möglicher Moderationseffekt der Klassenkomposition in Bezug auf das Verhalten überprüft. Hierzu wurden N = 719 Schülerinnen und Schülern der fünften und sechsten Jahrgangsstufe unter Verwendung der experience sampling method zu zwei bis drei Messzeitpunkten pro Tag an fünf aufeinanderfolgenden Schultagen zu ihrem aktuellen emotionalen Erleben und ihrem sozialen Kontext befragt. Insgesamt lagen 8870 „Momentaufnahmen“ des emotionalen Erlebens und von Unterrichtssituationen vor. Auf der Grundlage von Verhaltenseinschätzungen durch Lehrpersonen wurden mittels latenter Profilanalysen drei Profiltypen innerhalb der Schülerschaft identifiziert: Jugendliche mit adaptivem, internalisierendem und externalisierendem Verhalten. Ergebnisse von Multilevel-Strukturgleichungsmodellen zeigen, dass Jugendliche in Unterrichtssituationen, in denen sie mit ihren Peers interagieren (z.B. in Partner- oder Gruppenarbeiten), motivierter und weniger gestresst sind als in Einzelsituationen. Für Jugendliche mit externalisierendem oder internalisierendem Verhalten ist dieser Effekt stärker ausgeprägt. Die geringfügigen, jedoch nicht signifikanten differenziellen moderierenden Effekte verweisen zudem darauf, dass der Zusammenhang des emotionalen Erlebens und der Peerinteraktionen für Jugendliche nicht durch ihr Klassenumfeld in Bezug auf prosoziales oder problematisches Verhalten moderiert wird. Die Ergebnisse werden sowohl methodisch als auch inhaltlich diskutiert, unter anderem in Bezug auf die Frage, ob und inwiefern Peers Quellen aktueller Motivation im Unterricht darstellen.
Keywords: Developmental and Educational Psychology

Editorial zur zweiten Ausgabe der HLZ - Knickenberg, Margarita; Störtländer, Jan Christoph (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Wir freuen uns, das zweite Jahresheft der HLZ vorlegen zu können. In diesem Editorial werden wir zunächst die 14 Beiträge dieser Ausgabe vorstellen und sodann aus der zurückliegenden Entwicklung der Zeitschrift Perspektiven auf das laufende und bevorstehende Arbeitsprogramm werfen, was neben der Jahresausgabe sowohl die Themenhefte der HLZ als auch weitere Publikationsorgane beinhalten wird.

Perceptions of Inclusion Questionnaire (PIQ) - Knickenberg, Margarita; Zurbriggen, Carmen (SCHULE inklusiv)

Digitalisierung, Medienbildung und Medienkompetenz. Verhältnisbestimmungen und Implikatioen für die Lehrerbildung und den Lehrerberuf - Herzig, Bardo (Digital?! Perspektiven der Digitalisierung für den Lehrerberuf und die Lehrerbildung (Beiträge zur Lehrerbildung und Bildungsforschung))

Institutionen der Medienpädagogik: Schule und Medien - Herzig, Bardo (Handbuch Medienpädagogik)

Dynamische Simulation von industriellen Kreislaufprozessen zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny Y. (Chemie Ingenieur Technik 92)

Entwicklung von Echtzeitmodellen für Kreislaufprozesse der chemischen Absorption - Fedorov, Alexander; Frei, Herrmann; Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Chemie Ingenieur Technik)

Entwicklung und Evaluation des strategieorientierten Förderkonzepts „Wortschatzsammler" im Unterricht - Ulrich, Tanja; Laßmann, I (Nur ein Wort? Diagnostik und Therapie von Wortabrufstörungen bei Kindern und Erwachsenen)

Was sich bewährt hat: Impulse zur klassenbasierten Umsetzung strategieorientierter Wortschatzförderung mit dem "Wortschatzsammler" - Laßmann, I; Ulrich, Tanja (Praxis Sprache)

"Wortschatzsammler" im Unterricht: Entwicklung und Evaluation eines strategieorientierten, unterrichtsintegrierten Förderkonzepts - Laßmann, I; Ulrich, Tanja (Vierteljahresschrift für Heilpädagogik und ihre Nachbargebiete)

Der 'zivile Klassizismus' Gottscheds und Lessings: Kritische Revision eines Oppositionsverhältnisses - Süwolto, Leonie (Johann Christoph Gottscheds Critische Dichtkunst im europäischen Kontext. (Germanisch-Romanische Monatsschrift/Beihefte 99))

Literarisches Skizzieren als Körperpoetik. Theodor Storms "Marthe und ihre Uhr" (1848) - Süwolto, Leonie (Poetik der Skizze. Verfahren und diskursive Verortungen einer Kurzprosaform vom Poetischen Realismus bis zur Frühen Moderne)

Johann Christoph Gottscheds Critische Dichtkunst im europäischen Kontext

,Ich gedenke dieses trefflichen Buches mit Fleiß allhier‘: Cervantes’ Don Quijote, der Roman und das Wunderbare in Gottscheds Critischer Dichtkunst - Schlieper, Hendrik (Johann Christoph Gottscheds Versuch einer Critischen Dichtkunst im europäischen Kontext. (Beiheft Germanisch- Romanische Monatsschrift, 99))

Zur Einführung: Johann Christoph Gottscheds Versuch einer Critischen Dichtkunst im europäischen Kontext - Schlieper, Hendrik; Süwolto, Leonie (Johann Christoph Gottscheds Versuch einer Critischen Dichtkunst im europäischen Kontext. (Beiheft Germanisch-Romanische Monatsschrift, 99))

Die Zivilisierung der Liebe: Zu Honoré d'Urfés „Astrée" - Steigerwald, Jörn (Romanistische Zeitschrift für Literaturgeschichte 44, 2020, 1/2)

Johann Christoph Gottscheds Versuch einer Critischen Dichtkunst im europäischen Kontext

Von Helden- und Scherzgedichten: Gottscheds Epenreflexion in der "Critischen Dichtkunst“ - Steigerwald, Jörn (Johann Christoph Gottscheds "Versuch einer Critischen Dichtkunst" im europäischen Kontext, (GRM-Beiheft 99))

'Les tendresses de l'amour humain'. Pierre Corneilles „Polyeucte" - Steigerwald, Jörn (Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters)

Montaignes Launen und Fantasien oder : Vom Erschreiben des Essays ("Essais" I.20; III.5) - Steigerwald, Jörn (Der Essay als 'neue Form')

Vergleichende Kulturanthropologie nach dem anthropologischen Schlaf: Charles-Victor de Bonstettens "L’homme du Midi et l‘homme du Nord“ - Steigerwald, Jörn (Das achtzehnte Jahrhundert, 2020, 1)

Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters (1630-1760) - Steigerwald, Jörn (Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters)

Une tragédie pour le Louvre: "La Poétique" de La Mesnardière - Steigerwald, Jörn (Littératures classiques 2020/3 (n° 103). La Mesnardière, un lettré de cour au XVIIe siècle)

Das Fest der Feste - die "Plaisirs de l'île enchantée" oder Versailles als Maßstab - Steigerwald, Jörn (Jahrbuch der Thüringer Schlösser und Gärten. Fürstliche Feste: Höfische Festkultur zwischen Zeremoniell und Amüsement)

Textprozeduren: Lesen und Schreiben. Praxis Deutsch 281

Textprozeduren. Werkzeuge für Schreiben und Lesen. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 281)

Wie neutral sind Berichte? Modalisierungsprozeduren in Ereignisberichten - Rezat, Sara (Praxis Deutsch 281)

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda V.; Heske, Julian Joachim; Kühne, Thomas; Schmidt, Johannes; Antonietti, Markus; López-Salas, Nieves (Carbon)
Keywords: General Chemistry; General Materials Science

Positionierungen in argumentativen Gesprächen und Briefen der Schule - Rezat, Sara; Grundler, Elke; Schmölzer-Eibinger, Sabine (Zeitschrift für Angewandte Linguistik)

CauseNet: Towards a Causality Graph Extracted from the Web - Heindorf, Stefan; Scholten, Yan; Wachsmuth, Henning; Ngonga Ngomo, Axel-Cyrille; Potthast, Martin (Proceedings of the 28th ACM International Conference on Information and Knowledge Management (CIKM 2020))

Comparison of Zero-Knowledge Range Proofs - Kramer, Paul

„Für meinen späteren Beruf als Lehrerin hat mir das einiges gebracht!“ –Professionalisierung Lehramtsstudierender für das Unterrichten neu zugewanderter Schüler*innen - Zierau, Cornelia; Dohmann, Olga; Jung, Ulla; Decker, Claudia; Niederhaus, Constanze (Theorie-Praxis-Verzahnung in der Lehrkräftebildung. Ergebnisse aus dem Netzwerk „Stark durch Diversität“)

Modul 5: Literarische Texte - Zierau, Cornelia; Kofer, Martina (Deutsch lernen: Sprechen – Zuhören – Lesen – Schreiben. Erweiterte Sprachfähigkeiten)

DaZ Sekundarstufe. Konzepte und Materialien, Heft 1/2020, hg. v. Cornelia Zierau: Übergänge gestalten – Neu Zugewanderte unterrichten